Chronic Obstructive Pulmonary Disease Mortality in Bladder Cancer Patients: A SEER-Based Competing Risk Analysis - Wang, Shunde; Ge, Chengguo (Urology Journal, 2024)
Purpose: This study was designed to evaluate risk of mortality from chronic obstructive pulmonary disease (COPD) in patients with bladder cancer (BC). Methods and materials: Data on patients diagnosed with BC by pathology between 2000 and 2016 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. Based on reference data from the general population, the standardized mortality rate (SMR) is calculated. Nelson-Aalen cumulative hazard curves were used for assessment of the risk of COPD mortality in BC patients. Multivariable competing risk models were conducted. The proportional hazards assumption was tested using Schoenfeld residuals, which were scaled and plotted over time for each risk factor. Results: A total of 237,563 BC patients were identified for further analysis from the SEER database, 5,198 of these patients experienced COPD mortality; the overall SMR for COPD mortality in BC patients was 1.58 (95% CI: 1.54-1.63). Age, race, year of diagnosis, histologic type, summary stage, surgery, marital status, college education level, and median household income independently predicted COPD mortality in BC patients. Conclusions: In comparison to the general population, the risk of COPD mortality is significantly higher in patients with BC. Pre-identification of high-risk groups and respiratory care provisions are important measures to effectively improve survival in this group of patients.